2009
DOI: 10.4064/cm114-1-6
|View full text |Cite
|
Sign up to set email alerts
|

The essential cover and the absolute cover of a schematic space

Abstract: Dedicated to B. V. M.Abstract. A theorem of Gleason states that every compact space admits a projective cover. More generally, in the category of topological spaces with continuous maps, covers exist with respect to the full subcategory of extremally disconnected spaces. Such a cover of a space is called its absolute. We prove that the absolute exists within the category of schematic spaces, i.e. the spaces underlying a scheme. For a schematic space, we use the absolute to generalize Bourbaki's concept of irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A map, between generalized spectral spaces, is spectral if the inverse image of any compact open subset is compact open. Borrowing notation from Rump and Yang [27], let us denote by DL 0 the category of all distributive 0-lattices with 0-lattice homomorphisms with cofinal 1 range, and by GSp the category of all generalized spectral spaces with spectral maps. Stone duality, originating in Stone [32], states an equivalence of categories between DL 0 and the opposite category of GSp.…”
Section: Stone Duality For Distributive Latticesmentioning
confidence: 99%
“…A map, between generalized spectral spaces, is spectral if the inverse image of any compact open subset is compact open. Borrowing notation from Rump and Yang [27], let us denote by DL 0 the category of all distributive 0-lattices with 0-lattice homomorphisms with cofinal 1 range, and by GSp the category of all generalized spectral spaces with spectral maps. Stone duality, originating in Stone [32], states an equivalence of categories between DL 0 and the opposite category of GSp.…”
Section: Stone Duality For Distributive Latticesmentioning
confidence: 99%
“…The theory of lattice-ordered real vector spaces, i.e., Riesz spaces, has had quite some impacts on functional analysis. [2,3] characterized many interesting topological structures of lattice-ordered groups. Gusić [4] showed that a lattice-ordered group can be equipped with C-topology with respect to an admissible subset C of positive elements, and presented many interesting ideas and results on the topological group properties of lattice-ordered groups.…”
Section: Introductionmentioning
confidence: 99%
“…So the quasicomponents of the absolute of X parametrize the refined irreducible components of X, i.e. its irreducible components together with certain embedded ones, both with possible multiplicities [34]. Our lifting theorem then shows that the passage from an abelian l-group to its strongly projectable hull can be regarded as a process of desingularization.…”
mentioning
confidence: 96%
“…This yields a characterization of an extremally disconnected space in terms of its space of quasicomponents, which is an extremally disconnected Tychonoff space (Corollary 5 of Theorem 3). If X is the underlying space of a scheme, the fibers of p X are generic, which implies that p X is a retraction [34].…”
mentioning
confidence: 99%
See 1 more Smart Citation